Analisis Prosedur Dan Persyaratan Pembiayaan Mudharabah di Bank Syariah Indonesia KCP Ujung Berung1 - Tiyana, Tasya; Husnah, Rofikotul; Rosinawati, Dian (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2023)
The distribution of financing is provided by the bank to anyone who needs it, both for individuals and the business world, by taking into account two principles, namely trust and prudence (prudent banking principle). The bank will ask for guarantees in order to ensure the ability and ability of its customers to pay off debts according to the agreed contract. In operation, the requirement to provide this guarantee is to ensure that the mudharib does not make any deviations in managing the funds provided by the bank. The purpose of this study was to find out the procedures and requirements for mudharabah financing at the Indonesian Sharia Bank KCP Ujung Berung1. The method used in this study uses a qualitative approach. The results of this study are that the procedures and requirements for mudharabah financing at Bank Syariah Indonesia KCP Ujung Berung1 comply with the provisions of fatwa 07/DSN-MUI/IV/2000 concerning Mudharabah Financing, and OJK standards regarding mudharabah financing. Mudharabah financing requirements with the flow of inspection as follows: a) The business feasibility of the customer is in accordance with BSI provisions; b) Mudharabah financing will be processed if the account officer and Branch Manager meet the requirements, and contact the prospective mudharib to determine when to review the business location and collateral location; c) The account officer prepares a financing analysis report, visit data, collateral review results; d) Analysis of mudharabah financing carried out according to procedures using the